AI FOR SUSTAINABLE DEVELOPMENT: INNOVATIONS & APPLICATIONS - Supriya Kumari; Anu Kumari; Waoo, Akhilesh A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial intelligence (AI) has become universal across various sectors, permeating every aspect of our lives regardless of age or profession. In this era of AI, it’s necessary to prioritize sustainable development and innovation in its application. While AI enables rapid completion of tasks alike human efficiency, it also raises concerns about increasing unemployment rates. However, AI serves as a powerful tool for decoding the universe, emphasizing the necessity of sustainable AI development. This review paper examines the critical role of Artificial Intelligence (AI) in advancing the Sustainable Development Goals (SDGs) across multiple sectors, including healthcare, education, urban planning, agriculture, energy, and environmental conservation. Through the utilization of AI technologies, such as predictive analytics and machine learning algorithms, transformative solutions are being implemented to address complex challenges and facilitate sustainable development. However, challenges such as ethical considerations, data privacy concerns, accessibility issues, and the digital divide must be addressed to ensure equitable and sustainable deployment of AI technologies for SDGs. This paper emphasizes the importance of interdisciplinary collaboration, continued investment, capacity building, and policy frameworks to maximize the positive impact of AI while mitigating potential risks and disparities. By prioritizing ongoing investment in AI for sustainable development, stakeholders can unlock its full potential and pave the way for a sustainable and inclusive future.